2008
DOI: 10.1534/genetics.108.087924
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Loci Mapping of Genome Regions Controlling Permethrin Resistance in the Mosquito Aedes aegypti

Abstract: The mosquito Aedes aegypti is the principal vector of dengue and yellow fever flaviviruses. Permethrin is an insecticide used to suppress Ae. aegypti adult populations but metabolic and target site resistance to pyrethroids has evolved in many locations worldwide. Quantitative trait loci (QTL) controlling permethrin survival in Ae. aegypti were mapped in an F 3 advanced intercross line. Parents came from a collection of mosquitoes from Isla Mujeres, México, that had been selected for permethrin resistance for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
88
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(93 citation statements)
references
References 45 publications
4
88
0
1
Order By: Relevance
“…The excess of heterozygotes at CCE1C might also be associated with duplication. However, in earlier studies we found that the segregation of alleles at the para locus 12 and three different CCE-C genes fit a single gene model. 19 Linkage disequilibrium among loci.…”
Section: Methodsmentioning
confidence: 64%
See 3 more Smart Citations
“…The excess of heterozygotes at CCE1C might also be associated with duplication. However, in earlier studies we found that the segregation of alleles at the para locus 12 and three different CCE-C genes fit a single gene model. 19 Linkage disequilibrium among loci.…”
Section: Methodsmentioning
confidence: 64%
“…The SNP identification, allele-specific polymerase chain reaction (PCR), melting curve conditions, and genotype readings followed published procedures. 11,12,21,22 Table 2 lists the names of the SNP markers, their VectorBase identification numbers, physical or genetic location in the genome (if known) and the primer sequences used for allele-specific PCR. We obtained SNP genotypes at 13 SNP loci in each mosquito.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A cotton ball saturated with 30% sugar-water was placed on the top of each container as an energy/water source. Using procedures established for mosquitoes, sand flies were held in these containers for 24 h prior to mortality being recorded (Saavedra-Rodriguez et al 2008). Mortality was scored as a complete cessation of movement (Perea et al 2009).…”
Section: Methodsmentioning
confidence: 99%